1992
DOI: 10.1152/jappl.1992.72.2.621
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and oxygen free radical formation during pulmonary ischemia-reperfusion injury

Abstract: In a companion study, we showed that 2 h of warm unilateral lung ischemia followed by reperfusion resulted in bilateral tissue injury, indicated by increases in extravascular density (EVD) and permeability, measured as the pulmonary transcapillary escape rate (PTCER) for radiolabeled transferrin. EVD and PTCER measurements were obtained with the quantitative imaging technique of positron emission tomography (PET). In the current study, we evaluated this increase in EVD histologically and correlated EVD and PTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 25 publications
2
34
0
1
Order By: Relevance
“…We determined 90 min ischemic time to be adequate in the present model according to the results of our pilot investigation. We believe 6 h reperfusion is too short, but 12 to 18 h will be enough to demonstrate the significant injury because of the leukocyteendothelium interaction and related free radical and cytokine reaction which take effect within this period [27,28]. In the present study, most of the injury parameters maintained a relatively stable plateau level at 18 h after reperfusion, thus proving our hypothesis.…”
Section: Discussionsupporting
confidence: 77%
“…We determined 90 min ischemic time to be adequate in the present model according to the results of our pilot investigation. We believe 6 h reperfusion is too short, but 12 to 18 h will be enough to demonstrate the significant injury because of the leukocyteendothelium interaction and related free radical and cytokine reaction which take effect within this period [27,28]. In the present study, most of the injury parameters maintained a relatively stable plateau level at 18 h after reperfusion, thus proving our hypothesis.…”
Section: Discussionsupporting
confidence: 77%
“…23 Previous in vitro studies have demonstrated that FGF-1 is released from cells in response to oxidative stress, 16,23,24 a pathologic condition that may involve inflammatory-mediated production of reactive oxygen-nitrogen species. 39,57,58 Our results demonstrate the increased immunoappearance of iNOS and nitrotyrosine in the ductal epithelium of pancreatic tumor tissue. This observation predicts that endogenous production of reactive nitrogen species, as evidenced by markers for NO and peroxynitrite, induces oxidative stress in the ductal epithelium of pancreatic adenocarcinoma.…”
Section: Commentmentioning
confidence: 51%
“…This could explain the underlying mechanisms of inflammation in both the dependent lung and the nondependent lung [3,34]. The nondependent lung remains completely atelectatic for a period of time, which is accompanied by hypoperfusion due to hypoxic vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%